USING NON-DECIMATED WAVELET DECOMPOSITION TO ANALYSE TIME VARIATIONS OF NORTH ATLANTIC OSCILLATION, EDDY KINETIC ENERGY, AND UKRAINIAN PRECIPITATION - Loboda N.S.; Glushkov A.V.; Khokhlov V.N.; Lovett L. (My University, 2006)
We employ a non-decimated wavelet decomposition to analyse inter-annual variations of the North Atlantic Oscillations (NAO) indices and relationship of these variations with both the Eddy kinetic energy contents (KE) in the atmosphere of Northern mid-latitudes and the precipitation in the different regions of Ukraine during July 1960-February 2003. Major advantage of using this tool is to isolate short- and long-term components of fluctuations. Such analysis allows revealing basic periodic behaviours for the NAO indices such as the 4-8-year and the natural change of dominant phase. The main results can be posed as follows. The most essential relationship between the NAO index and KE content is found for the low frequency variations with the periods of 4-8 and 8-16 years, at that if the NAO phase tends to abrupt changes then the impact of these changes on the KE content is more significant than for the durational dominance of certain phase. The largest coefficients of correlation for the NAO index and Ukrainian precipitation are stated for the periodicities of 2-4 and 4-8 years; the former is caused by the synoptic-scale activity forced by the NAO while the former is conditioned by the air-mass processes in the warm season. © 2005 Elsevier B.V. All rights reserved.
Keywords: EDDY KINETIC ENERGY; NORTH ATLANTIC OSCILLATION; PRECIPITATION; UKRAINE; WAVELET ANALYSIS